EVALUATION OF WATERING REGIMES AND DIFFERENT POT SIZES IN THE GROWTH OF PARKIA BIGLOBOSA (JACQ) BENTH SEEDLINGS UNDER NURSERY CONDITION - F.A, Sale (European Scientific Journal, ESJ, 2015)
The study was carried out to investigate the effect of watering regimes and pot size on the growth of potted seedlings of Parkia biglobosa (JACQ) Benth. The experiment was set up using 3 x 4 Factorial experiment in Completely Randomized Design (CRD). Four different watering regimes were used: watering once daily, watering once in three days, watering once in five days and the control that was not watered. Three different pot sizes were used: the small size, medium and the large size. The parameters measured were subjected to Analysis of Variance (ANOVA). The means were separated by Least Significant Difference (LSD; Pâ‰¤0.05). The results showed that the best performance of Parkia biglobosa in terms of pot size was Medium Pot size (P2) which had 246.20 cm at the 10th week after transplanting, the poorest growth was recorded in the small pot size with the height of 16.55 cm in the 10th weeks after transplanting. Also the result showed that watering once in five days (W3) had the highest height of 19.96 cm followed by watering once daily (W1) with the height of 18.72 cm while the control (W0) had the least height of 16.21 cm.